PENGARUH MOTIF PENGGUNAAN APLIKASI HALODOC TERHADAP KEPUASAN PENGGUNA DALAM LAYANAN KESEHATAN - Jihan Thalia, (2021)
The development of information and communication technology makes all fulfillment of daily needs can be done anytime and anywhere. Seeing the conditions during the Covid-19 pandemic, all health services fulfillment has limitations. This is used by Halodoc to maximize its services. During the Covid-19 pandemic, the Halodoc application experienced an increase in users, this illustrates that the audience uses the media according to certain motives to meet their needs. This study aims to determine the influence of the motive for using the Halodoc application on user satisfaction. In theory Uses and Gratification audience basically using the media based on certain motives, which the media considered trying to meet the needs of the audience. This research uses explanative quantitative research methods, data collection techniques using surveys and questionnaires as instruments with a total sample of 100 respondents. To know how much influence these two variables, the researchers used a simple linear regression analysis. For data processing questionnaire, carried out using statistics program Product And Service Solution (SPSS) Windows version 25. Based on simple linear regression results for this study, the regression coefficient values obtained in this study is Y = 8,051 + 0.846x and 84,1 % for coefficient determination result. That means, there is the effect of being among the motives use online applications to user satisfaction remaining 15,9% influenced by other indicators that are not included in this study. Thats mean H0 is rejected and Ha is accepted.